Responses of the Murine Myeloid Colony-Forming Cell to Ansamycin Antibiotics - Horoszewicz, Julius S. (1974)
The in vitro susceptibility of murine myeloid colony-forming cells to the antiproliferative activities of three ansamycin antibiotics was determined. These cells were found to be 10- to 40-fold more susceptible than the corresponding human ones.